Effect of dried and extrudate of bitter gourd fruit on epithelial microflora in raw chicken legs meat - Abdelkarim, H.; Rukayadi, Yaya; Abdulkarim, S. M.; Sulaiman, Rabiha (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Plants have been used recently to eliminate bacterial growth in food products. This study was undertaken to test the in vitro sanitizing effect of crude extract from bitter gourd (BG) fruit on the growth of native microorganisms in raw chicken leg meat. Hot air dried BG and extrudate extracts at 1% concentration and exposure times of (5, 10 and 15 min) were used to treat the samples using dilution method. Results showed that BG extrudate had a slightly stronger bactericidal activity against the microflora than the B.G. hot air drying treatment, especially, on E. coli at all exposure time. Overall, there is no significant difference between the treatments; Total Plate Count (TPC), Escherichia coli, Bacillus cereus, Staphylococcus aureus. The best reduction time of microflora by hot air dried extract was at (15 min) except for B. cereus was at (5 min) and for extrudate extract was at (5 min) except for E. coli was at (10 min). In conclusion, bitter gourd extract could be used as an important natural sanitizer for rinsing raw food matrials such chicken meat.